Monday

April 21, 2014

April 21, 2014

Posted by **Cam** on Wednesday, April 10, 2013 at 8:44pm.

f(x)= t^2e^(-2t)

- Calculus -
**Reiny**, Wednesday, April 10, 2013 at 9:05pmprobably a type, f(x) should be f(t)

f ' (t) = t^2 (-2)e^(-2t) + 2t (e^(-2t))

= -2t e^(-2t) (t-1)

or

= (2t - 2t^2) e^(-2t)

now use the product rule again and simplify similar to what I did above

**Related Questions**

calculus - Find the derivative of the function 1)f(t)=tan(e^2t)+e^tan2t f'(t)= [...

calculus - Find the second derivative of the function: y=e^-2t*cos^2(t+(pi/4))

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Find the RMS value of the function i=15[1-e^(-1/2t)] from t=0 to t=4 ...

Math-Calculus (check please) - FOr the function f(x)=x^2e^x Find the critical ...

Applied Calculus - Find the first and second derivative of the function: x/(7x+...

Calculus - position function is x(t)=(t-1)^3 (2t-3) how do you find the velocity...

calculus - You are given the following function. f(x)= (8+x)/(1-8x) (a) Find the...